Analisis Pengembangan Kluster Bisnis Sepatu (Studi Kasus Industri Sepatu di Kecamatan Ciomas) - Dhina Ermayani; Aida Vitayala S Hubeis; Ma'mun Sarma (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2010)
The District of Bogor has potency as a human resources for shoes industry. Ciomas district is one of the central of shoes industry in Bogor. With all the potencies, the shoes industry is potential to be developed as one of export commodities. However, in reality, it is hard to grow because of some constraints, such as marketing and financial factors. The aim this research is : (1) to identify shoes industry in Ciomas Sub district, (2) to identify internal and external factor, (3) to formulate industrial expansion strategy of shoes in Ciomas Sub district. Research was executed in some small shoes industries at Ciomas Sub district in Bogor District. The data were collected from April to July 2008 including primary and secondary data. Primary data were obtained through field survey, interview with the owner of shoes industry and raw material supplier, while secondary data were obtained through book studying, related document and institution report. Information data of small industry were analyzed by using descriptive analysis, while quantitative data were analyzed by using IFE (Internal Factor Evaluation) Matrix, EFE (External Factor Evaluation) Matrix, IE (Internal External) Matrix, SWOT (Strength-Weakness-Opportunities-Threats) Matrix, and QSPM (Quantitative Strategic Planning Matrix). Small industry (IK) of self-supporting business shoes of Ciomas is a “CV” form having its own financial capital without existence of partnership with number of labors ranges from 6-12 stripper and established for 5-10 years. It does not depend on collector, either raw material or marketing. Small industry of shoes worker Ciomas is a workshop doing cooperation with collector in procuring financial capital, production order and marketing. The number of labors which were employed by IK worker less than 6 people and established for less than 5 year. The strategy that can be applied by self-supporting business was balancing quality and showing up its characteristic to anticipate business emulation, extending market share in other big towns of Indonesia using promotion media, innovation and various product to increase selling price by utilizing technology, working with banking to develop business, introducing trade mark to promote product, having collaboration with related government or institution to increase managerial ability, monetary management and marketing, handling all production process to increase profit, using technology to increase production and extends market share. The strategy that can be applied by IK worker was searching other capital sources to decrease the dependency to wholesaler, having collaboration with related government or institution to increase managerial ability, monetary management and marketing, balancing quality and showing up its characteristic to anticipate business emulation, introducing trade mark to promote product, innovating various product to increase selling price by utilizing technology, producing qualified products and intensive in searching opportunity to sell product, apart from collector.